2017
DOI: 10.1007/s13280-017-0910-1
|View full text |Cite
|
Sign up to set email alerts
|

On the tragedy of the commons: When predation and livestock loss may improve the economic lot of herders

Abstract: This paper studies the practice of semi-domestic reindeer (Rangifer t. tarandus) herding in Finnmark county in northern Norway. In this area, the Saami reindeer herders compete for space and grazing areas and keep large herds, while at the same time, the reindeer population is heavily exposed to carnivore predation by the lynx (Lynx lynx), the wolverine (Gulo gulo), and the golden eagle (Aquila chrysaetos). It is demonstrated that predation actually may improve the economic lot of livestock holders in this unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Management policy has been supported and encouraged by evidence of poor body growth of reindeer and of density-dependent changes in the biomass and botanical composition of reindeer pasture, especially in the north of the country (Fauchald et al, 2004;Bråthen et al, 2007;Ims et al, 2007;Tømmervik et al, 2009). These perceived evils have been attributed to overgrazing associated with their being 'too many reindeer' (e.g., Office of the Auditor General, 2004; Riseth and Vatn, 2009;Pape and Löffler, 2012;Benjaminsen et al, 2016b, Skonhoft et al, 2017. From this interpretation stems policy and legislation aimed specifically at reducing numbers of reindeer and thereby in some unspecified way achieving 'ecological, economic and cultural sustainability' of reindeer pastoralism (Government of Norway, 1992; see also Tyler et al, 2007).…”
Section: Human Intervention On Reindeer Pasture: Out Of Sight Out Of Mindmentioning
confidence: 99%
“…Management policy has been supported and encouraged by evidence of poor body growth of reindeer and of density-dependent changes in the biomass and botanical composition of reindeer pasture, especially in the north of the country (Fauchald et al, 2004;Bråthen et al, 2007;Ims et al, 2007;Tømmervik et al, 2009). These perceived evils have been attributed to overgrazing associated with their being 'too many reindeer' (e.g., Office of the Auditor General, 2004; Riseth and Vatn, 2009;Pape and Löffler, 2012;Benjaminsen et al, 2016b, Skonhoft et al, 2017. From this interpretation stems policy and legislation aimed specifically at reducing numbers of reindeer and thereby in some unspecified way achieving 'ecological, economic and cultural sustainability' of reindeer pastoralism (Government of Norway, 1992; see also Tyler et al, 2007).…”
Section: Human Intervention On Reindeer Pasture: Out Of Sight Out Of Mindmentioning
confidence: 99%
“…Mattisson et al (2011) conclude that semidomestic reindeers are the main prey for lynx in northern Scandinavia. The impact of predation is analyzed in Skonhoft, Johannesen, and Olaussen (2017). They study the steady state (equilibrium) in an age-and sex-structured reindeer population model and find that predation may improve the livestock holders economic result.…”
Section: Possible Extensionsmentioning
confidence: 99%
“…Cultural norms that identify species as ‘pest’ or ‘beneficial’ do not always reflect the actual contribution to ecosystem services supply and human well‐being (Saunders et al., 2016). For example, predation of livestock by wild mammals is nearly always perceived to be a disservice; however, in Saami reindeer systems in Norway, Skonhoft, Johannesen, and Olaussen (2017) showed that losses of reindeer to wild predators can be economically beneficial to human herders, as it may compensate for natural mortality and increase feeding conditions for remaining livestock. Conversely, government policies to maintain alien vertebrate populations in Australian national parks prioritize a cultural benefit to a small specialized community (e.g.…”
Section: Future Directions: Defining and Measuring Ecosystem Disservicesmentioning
confidence: 99%